Estrategias para fomentar la participación en actividades físicas y recreativas en alumnos del décimo año de la Unidad Educativa Francisco Huerta Rendón - GARCÍA ALVARADO ANYILY SELENA (2024)
This study focused on investigating the strategies implemented to promote participation in physical and recreational activities among tenth-grade students at the Francisco Huerta Rendón Educational Unit. The general objective was to determine effective strategies to increase student participation in these activities. Key factors influencing participation were identified, strategies tailored to students' preferences and interests were designed, and the effectiveness of these strategies was evaluated. The methodology involved administering structured surveys to a sample of 73 students, allowing for the collection of quantitative data on participation frequency, motivation, and perceptions of the offered physical activities. The results revealed that the implemented strategies, including personalized motivation techniques and diversification of activities based on student interests, had a significant positive impact. There was an observed increase in regular participation in physical activities and an improvement in students' positive perception of these activities. It was highlighted that physical activities not only contributed to students' physical and mental well-being but also positively correlated with academic performance. This finding underscores the importance of integrating physical and recreational activities into the educational environment to promote holistic student development.